2010
DOI: 10.1139/f10-016
|View full text |Cite
|
Sign up to set email alerts
|

Potential and realized interactions between two aquatic invasive species: Eurasian watermilfoil (Myriophyllum spicatum) and rusty crayfish (Orconectes rusticus)

Abstract: With multiple invasions, the potential arises for interactions between invasives inhibiting or promoting spread. Our goal was to investigate the interaction between two invasives, Eurasian watermilfoil (Myriophyllum spicatum) and rusty crayfish (Orconectes rusticus), which co-occur in several lakes in western Quebec, Canada, and to determine their overlap with littoral fish communities. Crayfish potentially aid milfoil dispersal by fragmentation or, alternatively, inhibit its proliferation through destruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…In a potential example of invasional meltdown, Maezo et al (2010) studied interactions between invasive M. spicatum and invasive crayfish Orconectes rusticus. They found positive and negative interactions between the species but noted that microhabitat partitioning would likely result in very little realized interaction.…”
Section: Mutualisms and Invasional Meltdownmentioning
confidence: 99%
“…In a potential example of invasional meltdown, Maezo et al (2010) studied interactions between invasive M. spicatum and invasive crayfish Orconectes rusticus. They found positive and negative interactions between the species but noted that microhabitat partitioning would likely result in very little realized interaction.…”
Section: Mutualisms and Invasional Meltdownmentioning
confidence: 99%
“…Exotic herbivores may also directly facilitate exotic plants via non-consumptive mechanisms. For instance, plant fragmentation may increase the dispersal of exotic plants (Maezo et al, 2010). A greenhouse study showed that mechanically generated A. philoxeroides' single-node fragments survived and grew in a moist soil mix, so fragmentation may increase the rate of spread of this clonal species (Dong et al, 2012).…”
Section: Reciprocal Facilitation Between Exotic Species (Imh)mentioning
confidence: 99%
“…For instance, exotic red deer (Cervus elaphus) and fallow deer (Dama dama) indirectly facilitated exotic Douglas fir (Pseudotsuga menziesii) by preferentially consuming the native evergreen conifer Austrocedrus chilensis (Relva, Nuñez & Simberloff, 2009). In addition, crayfish (Orconectes rusticus) may facilitate the invasion of exotic Eurasian watermilfoil (Myriophyllum spicatum) by increasing plant fragmentation (non-consumptive) (Maezo, Fournier & Beisner, 2010). Likewise, exotic plants may facilitate exotic herbivores by providing a higher quality food source (Engelkes & Mills, 2013) or by supplying higher quality substrata for reproduction (Burks, Kyle & Trawick, 2010) or shelter (Sessions & Kelly, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…); factors that influence water quality, number of game fish, number and type of boat ramps, bedrock type, littoral area, water source, number of residences, and proximity to roads (Buchan and Padilla ); distance to nearest invaded waterway, lake size, alkalinity, Secchi depth, and lake depth (Roley and Newman ); riparian use, interaction with other IS, substrate material, and debris (Maezo et al. ); wave action, water‐level drawdown, photic zone depth, aquatic vegetation shading, and native species present (Olson et al. ).…”
Section: Introductionmentioning
confidence: 99%